The effects of trade openness on Malaysian exchange rate - Lee, Chin; Law, Chee Hong (Serials Publications, 2013)
This study investigates the impact of trade openness on Mala ysian exchange rate. The findings show that most of the variables are statistically significant and carried the expected signs. As predicted by the theory, the rise of the income level and stock market index in Malaysia will lead to the appreciation of domestic currency. On the other hand, the increase in trade openness and interest rate can lead to depreciation of Malaysian Ringgit. In addition, the results suggested that a rise in money supply differential caused RM to appreciate. However, increase in trade balance caused the depreciation of RM.